Method and system for extracting and visualizing graph-structured relations from unstructured text - Hassan Awadalla, Hany; Mostafa, Hala (2005)
The present invention is directed to a system, method and computer program for automatically extracting and mining relations and related entities from unstructured text. A method in accordance with an embodiment of the invention includes: extracting relations and related entities from unstructured text data, representing the extracted information into a graph, and manipulating the resulting graph to gain more insight into the information it contains. The extraction of relations and related entities is performed first by automatically inducting pattern and second by applying these induced patterns to unstructured text data. For each relation and entity, several features are extracted in order to build a graph whose nodes are entities and edges are relations.
US7730085B2 US Grant